Answer:
a. x=2√3+3 and x = - 2√3 +3
b. x=29.5
c. x=2/3, x= - 2
d. x=25
Step-by-step explanation:
a). -2(x-3)² +5 = - 19
- 2(x-3)² = -19 - 5
- 2(x-3)² = - 24
(x-3)² = 12
x-3 = √12 and x-3 = -√12
x-3 =2√3 and x-3= -2√3
x=2√3+3 and x = - 2√3 +3
b)
[tex]\frac{\sqrt{2x+5} }{4} +1=3\\\\\\\frac{\sqrt{2x+5} }{4} =2\\\sqrt{2x+5} =8\\\\(\sqrt{2x+5} )^{2}=8^{2}\\2x+5=64\\2x= 59\\x=29.5[/tex]
c)
-5|3x+2| - 4 = -24
-5|3x + 2| = - 20
|3x +2| = 4
3x+2=4 or - (3x+2)=4
3x=2 or 3x+2 = - 4
x=2/3 or 3x = - 6, x= -2
d)
[tex]5\sqrt[3]{x+2} -7=8\\\\5\sqrt[3]{x+2} =15\\\\\sqrt[3]{x+2} =3\\x+2 = 3^{3}\\x+2=27\\x=25[/tex]